(untitled) (Research, Society and Development, 2022)
Objective: The objective of the presented study was to describe a clinical case of a male patient, 45 years old, diagnosed with colorectal adenocarcinoma, however, in stage IV, with the presence of liver and lung metastases. Methodology: This case was carried out in a retrospective, descriptive and observational manner, by direct collection of patient data through access to medical records, patient interview and results of complementary exams. Case description: Patient, A.A.S.F, 45 years old, complaining about abdominal cramps, rectal tenesmus and ribbon stools who was diagnosed with Metastatic Colorectal Adenocarcinoma in 2011, therefore, with a follow-up of approximately ten years. In this case, several therapies were used and several chemotherapy sessions were performed with the aim of remission of the disease. In addition, imaging tests, for example, PET CT, were of paramount importance for the management of the case, in addition to the measurement of serum levels of the tumor marker CEA. Conclusion: Severe cases like this require different approaches, and early diagnosis is important for more favorable prognoses. The patient, having been diagnosed late, evolves with liver and lung metastases, making treatment difficult, which required a very aggressive therapeutic approach.